Infection Helicobacter pylori and stomach cancer: state-of-the-art - A. A. Sheptulin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To carry out analysis of the publications devoted to Helicobacter pylori infection and stomach cancer (SC) interrelation.Original positions. Available data convincingly confirm that Н. pylori infection increases risk of SC development, however in close interaction with host factors – genetic factors, dietary habits, etc. Eradication of Н. pylori results in decrease of atrophic gastritis severity, but does not affect intestinal metaplasia process. Nowadays it is indicated for patients with high risk of SC (having atrophic gastritis, postgastrectomy patients for early SC, first-degree relatives of patients with SC).Conclusion. Pathophysiological and clinical aspects of interrelations between Н. pylori infection and SC require the further studies.